Senior High School Biology Teachers’ Perception towards Evolution Learning - Darussyamsu, Rahmawati; Wahyuni, Resma; Fitri, Rahmadhani; Fadilah, Muhyiatul; Putri, Dwi Hilda; Mukhtar, Mukhtar (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2019)
Teachers’ perception of a particular material is an influential aspect of the way teachers learn the material. Since evolution is a debating material, teachers affected by this condition when they teaching the evolutionary topic. For those reasons, this descriptive study aimed to identify teachers’ perception of evolution learning, which consists of four main aspects: learning material, strategy, sources, and assessment. The population is all biology teachers at Padang, Sumatera Barat, Indonesia. Sampling was taken by purposive sampling, with criteria biology teachers that already taught the evolutionary topic in senior high school. Data collected from the questionnaire and analyzed descriptively in percentage. The result showed that for the majority of biology teachers at Padang have perceptions toward four aspects of evolution learning in a category very good, good, and good enough. In details, more concerns are needed for some less valued descriptor related to the contradiction issue between evolution theory and Islamic beliefs. In the average, each score of perception for four aspects are: learning material 3.71; strategies 4.11; sources 3.64; and assessment 3.92 with all average criteria in good category. Each aspect performed is discussed.